Training strategies in search of a socially responsible University - Henríquez-Fuentes, Gustavo; Higuera-Ojito, Víctor Hugo; Rosano Reyes, Enrique; Robles, Nilka; Aragaki, Alfredo (Corporación Universitaria Americana, 2019)
The objective of the study is to design a strategy of Corporate Social Responsibility (hereinafter RS) based on the expectations of students in higher grades of different programs of a private university in Barranquilla. Based on a correlation and clustering analysis, students' expectations of SR in the university are analyzed and classified. Among the most noteworthy results, the importance of variables with high correlation that should be prioritized in the order of investments and measurements, due to their influence with other variables is demonstrated. The study provides a definition of SR from the theoretical contribution and empirical data obtained in the research, also proposing a Social Responsibility strategy applicable to a University. Curricular reforms, relationship with the community, support for the development of teachers and the constant development of evaluation and monitoring processes regarding Social Responsibility are exposed.